TOOL CHANGING MECHANISM FOR MACHINE TOOL - LIU CHE SEN (2014)
A machine tool includes a receptacle extended from a stand, a working spindle rotatably attached to the receptacle and having a chuck device for grasping and releasing a tool member from the working spindle, a follower slidably attached onto the working spindle for actuating the chuck device to selectively grasp or release the tool member, a lever arm having one end pivotally attached to the receptacle with an axle, an actuator attached to the lever arm for actuating the follower to operate the chuck device to grasp and to release the tool member, and a driving device includes a piston for moving the lever arm and the actuator to actuate and move the chuck device to release the tool member.